Building Institutional Capacity for Implementing the National Climate Change Strategy in Romania - World Bank Group (World Bank, Washington, DC, 2016)
Romania has already been affected by climate change. The IPCC projections indicate that the climate will warm up over this century at least in line with global projections and precipitation patterns will shift so as to make winters wetter and summers drier. Already, in 2007, Romania experienced the warmest year in two decades (average temperature 11.5° C against a 25 year average of 8.4° C) and the most severe drought in the last 60 years while in 2005 there were historic floods, which caused 76 deaths and significant property damage. The effects of these extreme weather events adversely affected the country through significant economic loss in agriculture, transport, energy supply, and water management. Consequently, mitigation and adaptation to climate change are increasingly important priorities for Romania. After the introduction chapter, the current situation as well as the CC commitments that Romania has undertaken are presented in chapter two. Chapter three provides the possible good practices that could provide inspiration for further reform. A contrast of the commitments with the current capacity and the available good practices has been substantiated in the analyses of capacity gaps that need to be addressed in chapter four. The next chapter provides the avenues for breaching those gaps and sustainably building CC capacity in order to ensure the smooth implementation of the strategy. Project management and financing is treated separately in chapter six since it has been an issue of particular concern and difficulty for the GoR. Finally, chapter seven sets out the basic elements of a public engagement campaign that will be essential for making CC a national issue present in the awareness of the public authorities, civil society and general public alike. A comprehensive list of the proposed measures and their time horizons can be found in annex one.